2013
DOI: 10.3892/etm.2013.1267
|View full text |Cite
|
Sign up to set email alerts
|

Malposition of peripherally inserted central catheter: Experience from 3,012 patients with cancer

Abstract: The aim of this study was to observe and analyze the causes of misplacement of peripherally inserted central catheters (PICCs) in patients with cancer. A total of 3,012 patients who underwent insertion of a PICC were reviewed from August 2000 to March 2012. The locations of the tube tips were recorded by chest X-ray examination. Malposition of the PICC was observed in 237 cases (7.87%), with the most frequently occurring site of misplacement being the jugular vein, followed by the axillary vein. By taking diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 11 publications
2
28
1
Order By: Relevance
“…Malposition of the catheter tip was observed in 10 % of the cases in their study [2]. In another study, malposition was seen in 7.87 % of the PICCs [3]. The use of USG to guide the insertion of PICCs is already established in oncology practice [4].…”
Section: Discussionmentioning
confidence: 95%
“…Malposition of the catheter tip was observed in 10 % of the cases in their study [2]. In another study, malposition was seen in 7.87 % of the PICCs [3]. The use of USG to guide the insertion of PICCs is already established in oncology practice [4].…”
Section: Discussionmentioning
confidence: 95%
“…Since the clinical introduction of PICC lines, reducing malposition has been a focus of clinical nursing practice. The incidence of malpositioned catheters is 5%-31%, which includes malpositioned catheters, catheter slides or extrusions, and catheter drifts (Song & Li, 2013). In the current study, the malposition rate was 8%, which is within the range proposed by other studies.…”
Section: Discussionmentioning
confidence: 99%
“…Many factors may influence PICC malposition. The literature shows that it has been related to age but not gender, puncture method, or lesion location (Song & Li, 2013 revealed that changing puncture position from supine posture to semirecumbent posture or sitting straight could reduce the incidence of malposition. In the current study, analyses of 2,084 cases revealed that age, gender, disease type, catheter type, and puncture method had no effect on incidence of malposition.…”
Section: Discussionmentioning
confidence: 99%
“…PICCs are often favored because of safety with insertion in the arm, compatibility with inpatient and outpatient therapies, ease of protocolization for insertion by vascular access nursing services, patient tolerability, and cost savings . Yet limitations of PICCs exist and complications including malpositioning, dislodgement, and luminal occlusion affect patient safety and outcomes. Most notably, PICCs are strongly associated with risk for thrombosis and infection, complications that are most frequent in hospitalized and critically ill patients …”
Section: Introductionmentioning
confidence: 99%